2020
DOI: 10.3389/fpubh.2020.00425
|View full text |Cite
|
Sign up to set email alerts
|

Political Consequences of COVID-19 and Media Framing in South Korea

Abstract: This study explored the Korean media's framing of COVID-19 and its impact on people's support for the government. A disaster such as a public health crisis has political consequences. COVID-19 is no exception. However, the direction of the effect is not easily determined. To properly understand this phenomenon, it is necessary to analyze how the media frames the crisis. Using Structural Topic Model, this study examines the Korean media's framing of COVID-19 and especially pays attention to international compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…People in collectivist societies not only hold personal responsibility to prevent COVID-19 infections, but also share collective responsibility to fight against the disease and contribute to the public good. As social media users continuously to be exposed to information about the unremitting efforts that the government and the community has made in response to the virus ( Molter & DiResta, 2020 ; Jo and Chang, 2020 ), they are likely to have a propensity to coordinate their actions. Third, due to the interactive nature of social media, people often encountered COVID-19 information through the interaction with other users.…”
Section: Discussionmentioning
confidence: 99%
“…People in collectivist societies not only hold personal responsibility to prevent COVID-19 infections, but also share collective responsibility to fight against the disease and contribute to the public good. As social media users continuously to be exposed to information about the unremitting efforts that the government and the community has made in response to the virus ( Molter & DiResta, 2020 ; Jo and Chang, 2020 ), they are likely to have a propensity to coordinate their actions. Third, due to the interactive nature of social media, people often encountered COVID-19 information through the interaction with other users.…”
Section: Discussionmentioning
confidence: 99%
“…Racism has also featured in some countries' news reporting, particularly against Chinese people, who have been frequently positioned as to blame for the emergence of the novel coronavirus in Wuhan [22]. Politicisation and polarisation of opinion has characterised COVID-19 news in US television networks and newspapers [23], whereas strong support for government measures was evident in South Korean newspaper reporting [24]. A focus on prevention and control measures, medical treatment and research, and global or local socioeconomic influences was identified in an analysis of Chinese news articles [25].…”
Section: Introductionmentioning
confidence: 99%
“…The frames are the central news angles through which the newspaper presented and tried to combat the dissemination of the virus. Each of the news angles is regarded as a frame such as: awareness, containment, panic, conspiracy, and political influence (Jo, Chang, 2020). Others are; effect, mobilization, support, misinformation, and boycott frames.…”
Section: Discussionmentioning
confidence: 99%